2021
DOI: 10.1016/s0140-6736(21)02183-8
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mRNA BNT162b2 COVID-19 vaccine up to 6 months in a large integrated health system in the USA: a retrospective cohort study

Abstract: Background Vaccine effectiveness studies have not differentiated the effect of the delta (B.1.617.2) variant and potential waning immunity in observed reductions in effectiveness against SARS-CoV-2 infections. We aimed to evaluate overall and variant-specific effectiveness of BNT162b2 (tozinameran, Pfizer–BioNTech) against SARS-CoV-2 infections and COVID-19-related hospital admissions by time since vaccination among members of a large US health-care system. Methods In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

113
1,038
7
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,111 publications
(1,164 citation statements)
references
References 34 publications
113
1,038
7
6
Order By: Relevance
“…At seven months past dose two for BNT162b2 we predict IgG levels to drop to 0.16 percent of the peak response; suggesting that 0.16% of the peak response correlates to 16% efficacy. In another BNT162b2 study, against infection was found to decline to 47% five months post dose two, with efficacy against the delta variant found to be 53% four months after full vaccination [37]. We find that following two standard doses of BNT162b2 the IgG counts have dropped to 2.1 and 7.2 percent of peak, five and four months following the second dose, respectively.…”
Section: Discussionmentioning
confidence: 54%
“…At seven months past dose two for BNT162b2 we predict IgG levels to drop to 0.16 percent of the peak response; suggesting that 0.16% of the peak response correlates to 16% efficacy. In another BNT162b2 study, against infection was found to decline to 47% five months post dose two, with efficacy against the delta variant found to be 53% four months after full vaccination [37]. We find that following two standard doses of BNT162b2 the IgG counts have dropped to 2.1 and 7.2 percent of peak, five and four months following the second dose, respectively.…”
Section: Discussionmentioning
confidence: 54%
“…Together, these data identify durable cellular immunity for at least 6 months after mRNA vaccination with persistence of high-quality memory B cells and strong CD4+ T cell memory in most individuals. These data may also provide context for understanding potential discrepancies in vaccine efficacy at preventing infection versus severe disease, hospitalization, and death (10,11). Declining antibody titers over time likely reduce the potential that vaccination will completely prevent infection or provide near-sterilizing immunity.…”
Section: Discussionmentioning
confidence: 99%
“…This decline from peak antibody levels may be associated with an increase in infections over time compared to the initial months post-vaccination (8, 9). Yet, vaccine-induced immunity remains highly effective at preventing severe disease, hospitalization, and death even at later timepoints when antibody levels may decline (10)(11)(12).Previous research has largely focused on responses early in the course of vaccination, with transcriptional analysis identifying potential links between myeloid cell responses and neutralizing antibodies (13).…”
mentioning
confidence: 99%
“…Since the end of December 2020, the World Health Organization (WHO) had identified several COVID-19 vaccines that have been shown to be efficacious in lowering the risk of contracting COVID-19 during controlled clinical trials in the WHO Emergency Use Listing [2]. As crucial tools in the pandemic response, COVID-19 vaccines also demonstrated accumulating evidence of protection against severe disease, hospitalization, and death [3][4][5]. While vaccination provides individuals protection against the virus [6], researchers also advocate a high-level community vaccination coverage to minimize the impact of COVID-19 on society [7].…”
Section: Introductionmentioning
confidence: 99%